Acute toxicity assessment of ANAMMOX substrates and antibiotics by luminescent bacteria test - Ding, Shuang; Wu, Junwei; Zhang, Meng; Lu, Huifeng; Mahmood, Qaisar; Zheng, Ping (Chemosphere (Oxford), 2015)
•Individual toxicities of ANAMMOX substrates and four antibiotics were introduced.•Joint toxicities of ANAMMOX substrates and four antibiotics were introduced.•Luminescent bacteria test is a new method for predicting integrated toxicity for ANAMMOX process. Acute toxicities of anaerobic ammonia oxidation (ANAMMOX) substrates and four antibiotics from pharmaceutical wastewaters on ANAMMOX process were reported. Individual and joint acute toxicity assays were performed using 50% inhibitory concentration (IC50). Results showed that IC50 values and their 95% confidence interval of ammonium chloride (A), sodium nitrite (B), penicillin G-Na (C), polymyxin B sulfate (D), chloramphenicol (E) and kanamycin sulfate (F) were 2708.9 (2247.9–3169.9), 1475.4 (1269.9–1680.9), 5114.4 (4946.4–5282.4), 10.2 (1.8–18.6), 409.9 (333.7–486.1) and 5254.1 (3934.4–6573.8) mgL−1 respectively, suggesting toxicities were in the order of D>E>B>A>C>F. Joint acute toxicities of bicomponent mixtures A and B, C and D, C and F, D and F were independent; D and E, E and F were additive while C and E were synergistic. Joint acute toxicities of multicomponent mixtures were synergistic or additive. Luminescent bacteria test is an easy and robust method for forecasting the feasibility of ANAMMOX process for pharmaceutical wastewater treatment.